Acetylation of Acacia Mangium Wood Fibres and its Application in the Medium Density Fibreboard - Unchi, Sining (1996)
The effective utilisation of low quality wood of Acacia mangium Willd. would be for the production of medium density fibre board (MDF). However, MDF is susceptable to biodegradation and dimensionally unstable when in contact with water, which is also associated with the deterioration of the mechanical and physical properties of the board. Nonetheless, research on wood has shown that it is possible to eliminate the biodegradation and dimensional in stability through chemical modification. This study was there fore conducted with the aim of evaluating the acetylation characteristics of Acacia mangium wood fibres and the properties and performances of the board produced. pilot acetylation was conducted to establish the optimum reaction conditions, which was subsequently used as a guide in the bulk acetylation of the fibres. Boards were manufactured from both the acetylated and unacetylated fibres and the properties and performances of the boards were evaluated.